Parkinsonism - Guimarães, João (2004)
The concept of parkinsonism is described. The principal clinical aspects of idiopathic Parkinson’s disease (PDI) and the criteria that support and/or exclude the diagnosis are outlined as well as some difficulties in the definition of this entity. The main differential diagnosesare summarised.